PERAN KELOMPOK SADAR WISATA DALAM PENGEMBANGAN WISATA BOTUBARANI KECAMATAN KABILA BONE KABUPATEN BONE BOLANGO - Sri Lestari Gintulangi (Universitas Muhammadiyah Gorontalo, 2019)
The aim of Role of Tourism Awareness Groups in the Development of Botubarani Tourism, Kabila Bone District, Bone Bolango Regency. This type of research is qualitative research using a descriptive approach. The data sources obtained are primary and secondary data. Data analysis techniques used data reduction, data exposure, and drawing conclusions.The results of this study indicate that, 1) The role of the Botubarani Awareness Group (Tourism Awareness Group) in the development of Botubarani Tourism to become a government partner in tourism development, Botubarani tourism development is the beneficiary of the development of Botubarani tourism, the Tourism Awareness Group becomes a driving force in society so that Being a friendly host, the Botubarani Tourism Awareness Group is a driving force in the community in realizing Sapta Pesona. 2) The concept of the Tourism Awareness Group organization in developing botubarani tourism with the community 3) The individual behavior of the Tourism Awareness Group in developing botubarani tourism as a social structure for the community. The Tourism Awareness Group always strives for equal distribution of benefits, the community is willing to work together to carry out programs and training but low human resources, and low awareness of tourists and the public in maintaining cleanliness In this study, it is concluded that the role of tourism awareness groups in the development of Botubarani tourism is qualitatively descriptive using 3 role indicators put forward by Livinson, quoted by Soerjono Soekanto, it can be said that the role of the tourism awareness group in developing Botubarani tourism is not optimal Keywords: Role, Tourism Awareness Group, Tourism Development